2011
DOI: 10.4314/br.v8i2.66889
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suitability of Wood Fibres of Four Nigerian Fruit Trees for Paper–Making

Abstract: Wood fibres of four fruit trees of Nigeria commonly found inNsukka metropolis were studied and assessed for their suitability for paper-making. These trees include Mangifera indica, Anacardium occidentale, Persea americana and Dacryodes edulis. The parameters used in the study were the fibre dimensions and derived fibre values. The mean values for fibre length of the species ranged from 0.89 ± 0.34 mm in Persea americana to 1.15 ± 0.38 mm in Dacryodes edulis; mean fibre lumen diameter of 0.009 ± 0.001 mm in An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Therefore, it is expected that P. biglobosa and M. excelsa produce poor paper. The RR values reported in this work are similar to other Nigeria timbers reported in previous works (Ezeibekwe, Okeke, Unamba & Ohaeri, 2009;Awaku, 1994;Ogunkunle, 2010;Oluwadare and Sotannde, 2007;Ajuziogu, Nzekwe & Chukwuma, 2010;Sadiku and Abdukareem, 2019).…”
Section: B Derived Fibre Morphological Indices Of the Wood Speciessupporting
confidence: 90%
“…Therefore, it is expected that P. biglobosa and M. excelsa produce poor paper. The RR values reported in this work are similar to other Nigeria timbers reported in previous works (Ezeibekwe, Okeke, Unamba & Ohaeri, 2009;Awaku, 1994;Ogunkunle, 2010;Oluwadare and Sotannde, 2007;Ajuziogu, Nzekwe & Chukwuma, 2010;Sadiku and Abdukareem, 2019).…”
Section: B Derived Fibre Morphological Indices Of the Wood Speciessupporting
confidence: 90%
“…For the coefficient of flexibility, the results were similarly recorded for Dacryodes edulis (0.57) by Ajuziogu et al (2010), Daniellia olivera (0.51) by Idu and Ijeomah (2000), and Leucaena leucocephala (0.63) by Oluwadare and Ashimiyu (2007). The coefficient of flexibility property is significant in producing pulp and paper.…”
Section: Discussion 41 Vessels Characteristicsmentioning
confidence: 59%
“…The good wood for pulp and paper production is expected to have a Runkel ratio of less or equal to 1 (Kpikpi, 1992). The Runkel ratio of A. senegal (0.99 µm) compares favorably to that of Anthonotha macrophylla (0.99 µm) and Dialium guineensis (0.99 µm) which are hardwood species in the Nigerian rainforest ecosystem (Ezeibekwe et al, 2009), and higher than the reported 0.79 µm for tropical Pinus species (Ajala, 1997) and 0.70 µm for Dacryodes edulis (Ajuziogu et al, 2010). A good wood suitable for pulping, must have fibres with satisfactory flexibility (Idu & Ijeomah, 2000).…”
Section: Discussionmentioning
confidence: 66%